ANALISIS HUBUNGAN MODAL SOSIAL TERHADAP KEBERDAYAAN PETANI KARET (Studi Kasus Petani Karet Di Kecamatan Gunung Toar Kabupaten Kuantan Singingi) - Bima Ferdinan Putra; Roza Yulida; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims to: 1) analyze the social capital owned rubber farmers, 2) analyze the empowerment owned rubber farmers, and 3) to analyze the relationship of social capital towards the empowerment of the rubber farmers. This research was conducted in Gunung Toar of District Kuantan Singingi of regency. The sampling method using purposive sampling technique with the count of respondents 85 farmers. Collecting data in this research by using interviews and surveys. The data analysis using descriptive methods. Score calculation of social capital and the empowerment of rubber farmers using Likert scale and the relationship between social capital towards the empowerment of rubber farmers using Spearman rank correlation analysis. The results shown from this research (1) social capital rubber farmers in Gunung Toar of District has a scored of 3.88 in the high category (2) empowerment of rubber farmers in in Gunung Toar of Districtscored 3.31 in enough category (3) the relationship of social capital to the empowerment of rubber farmers as a whole has a very weak correlation. Thus, the high social capital is not unduly influence on the empowerment of rubber farmers in Kuantan Singingi. The problem that occurs is the lack of empowerment of rubber farmers in the Gunung Toar district. So the government in this case, have to cooperated with related institution to implement the empowerment process and fulfill the infrastructure is inadequated for the rubber farmers. Keywords : Social Capital, Empowerment, Rubber Farmers